2004
DOI: 10.1039/b407358d
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence properties of isolated rat hepatocytes under different metabolic conditions

Abstract: The contribution of endogenous fluorophores - such as proteins, bound and free NAD(P)H, flavins, vitamin A, arachidonic acid - to the liver autofluorescence was studied on tissue homogenate extracts and on isolated hepatocytes by means of spectrofluorometric analysis. Autofluorescence spectral analysis was then applied to investigate the response of single living hepatocytes to experimental conditions resembling the various phases of the organ transplantation. The following conditions were considered: 1 h afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 43 publications
2
72
0
Order By: Relevance
“…The cell selection criteria were the same as described above. In the course of these studies we encountered cells in which there was notable autofluorescence as previously observed by others (31). Autofluorescence is visible in all channels but is much weaker in the infrared channel.…”
Section: Immunofluorescence Studiesmentioning
confidence: 56%
“…The cell selection criteria were the same as described above. In the course of these studies we encountered cells in which there was notable autofluorescence as previously observed by others (31). Autofluorescence is visible in all channels but is much weaker in the infrared channel.…”
Section: Immunofluorescence Studiesmentioning
confidence: 56%
“…NADH is highly autofluorescent when illuminated with UV light (366 nm), but its oxidized form, NAD þ , is not. This is why the fluorescence intensity of NADH is widely used to assess the hepatocellular metabolic status (Barlow and Chance, 1976;Croce et al, 2004;ObiTabot and Hanrahan, 1993;Paxian et al, 2004). In our study, changes in the NADH fluorescence intensity were quantified after 15 min of exposure to single gas supply.…”
Section: Discussionmentioning
confidence: 99%
“…A decreased O 2 tension is paralleled by decreases in the concentration ratio of nicotinamide adenine dinucleotide (NAD) compared to its reduced form (NADH). As such, the autofluorescence of NADH has been widely used as an indicator of cellular metabolic status to elucidate the states of both hepatic tissue and cells under hypoxic conditions (Chandel and Budinger, 1997;Croce et al, 2004;Obi-Tabot and Hanrahan, 1993;Paxian et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This showed that non-vital cardiomyocytes no longer possess CA activity and thus do not contribute to the mass spectrometric signal. In the case of hepatocytes, we were not able to use DNSA staining because of the very high auto-fluorescence of hepatocytes [19]. For hepatocytes, we use an alternative approach.…”
Section: Resultsmentioning
confidence: 99%